Evidence for Glacial Refugia of the Forest Understorey Species Helleborus niger (Ranunculaceae) in the Southern as Well as in the Northern Limestone Alps - Záveská, Eliška; Kirschner, Philipp; Frajman, Božo; Wessely, Johannes; Willner, Wolfgang; Gattringer, Andreas; Hülber, Karl; Lazić, Desanka; Dobeš, Christoph; Schönswetter, Peter (Frontiers in Plant Science, 2021)
Glacial refugia of alpine and subnival biota have been intensively studied in the European Alps but the fate of forests and their understory species in that area remains largely unclear. In order to fill this gap we aimed at disentangling the spatiotemporal diversification of disjunctly distributed black hellebore Helleborus niger (Ranunculaceae). We applied a set of phylogeographic analyses based on restriction-site associated DNA sequencing (RADseq) data and plastid DNA sequences to a range-wide sampling of populations. These analyses were supplemented with species distribution models generated for the present and the Last Glacial Maximum (LGM). We used exploratory analyses to delimit genomically coherent groups and then employed demographic modeling to reconstruct the history of these groups. We uncovered a deep split between two major genetic groups with western and eastern distribution within the Southern Limestone Alps, likely reflecting divergent evolution since the mid-Pleistocene in two glacial refugia situated along the unglaciated southern margin of the Alps. Long-term presence in the Southern Limestone Alps is also supported by high numbers of private alleles, elevated levels of nucleotide diversity and the species’ modelled distribution at the LGM. The deep genetic divergence, however, is not reflected in leaf shape variation, suggesting that the morphological discrimination of genetically divergent entities within H. niger is questionable. At a shallower level, populations from the Northern Limestone Alps are differentiated from those in the Southern Limestone Alps in both RADseq and plastid DNA data sets, reflecting the North-South disjunction within the Eastern Alps. The underlying split was dated to ca. 0.1 mya, which is well before the LGM. In the same line, explicit tests of demographic models consistently rejected the hypothesis that the partial distribution area in the Northern Limestone Alps is the result of postglacial colonization. Taken together, our results strongly support that forest understory species such as H. niger have survived the LGM in refugia situated along the southern, but also along the northern or northeastern periphery of the Alps. Being a slow migrator, the species has likely survived repeated glacial-interglacial circles in distributional stasis while the composition of the tree canopy changed in the meanwhile.